Magnetic resonance spectroscopy of hippocampal and striatal neurometabolites in experimental PTSD rat modeling - V. E. Tseilikman; O. B. Shevelev; N. V. Khotskin; A. S. Dotsenko; G. V. Kontsevaya; M. S. Lapshin; M. P. Moshkin; M. V. Komelkova; I. V. Feklicheva; O. B. Tseilikman; E. Dremencov; E. L. Zavjalov (Вавиловский журнал генетики и селекции, 2017)
The spectrum of the metabolites in the dorsal region of the hippocampus and striatum was studied using the method of 1H magnetic resonance spectroscopy at experimental modeling of the posttraumatic stress disorder syndrome (PTSD) in rats. PTSD was reproduced by exposure of the cat cue to rats daily along 10 day by 10 minutes at once. The anxiety level of animals was estimated 12 days later after the end of the experimental series of stress. Based on the anxiety index, the rats were divided into 3 phenotypes. The animals with an anxiety index > 0.8 (group 1) had lower plasma corticosterone compared with rats form the control group. In animals with an anxiety index in the range 0.7–0.8 (group 2), an elevated corticosterone level was noted. The rats with an anxiety index < 0.7 (group 3) had a lower plasma corticosterone level compared with animals from the control group. Rats of group 2 were characterized by an increased level of GABA in the hippocampus compared with controls. In the remaining groups, the percentages of GABA in the hippocampus and striatum did not differ significantly from the control. The distribution of NAA differed form that of GABA. The highest level of NAA was found in the striatum for rats from group 1, whereas NAA in animals form groups 1 or 3 did not differ from the control. The NAA level in the hippocampus was similar between all groups, including the control. The results obtained indicate that multiple exposures to psychological stress associated with the sense of proximity of a natural enemy in some animals cause an anxiolytic reaction. These animals are characterized by a stable corticosterone level and a stable level of neurometabolites in the studied structures of the brain. For rats with the highest level of anxiety, a lowered level of corticosterone with a constant level of neurometabolites in the hippocampus and striatum is characteristic. And only in rats with an intermediate level of anxiety, synchronization was observed between the increase in plasma corticosterone and the increase in hippocampal GABA content. The results obtained are in good agreement with the ideas of the protective action of glucocorticoids under PTSD manifested in  restraining violations of the psycho-physiological status. The mate rials allow the neurobiological mechanisms of the protective action of glucocorticoids to be detailed.